Implications of Smart Logistics in Nanostores: A Meta-analysis of Challenges and Opportunities for Industry 5.0 and Society 5.0 - Ortega-Jimenez, Cesar H; Sabillon Palomeque, Dany N.; Melgar-Martínez, Narciso A (LACCEI, 2024)
The increasing emphasis on human-centricity and adaptability has driven scholarly exploration beyond the technology-centric focus of Industry 4.0, leading to the emergence of Industry 5.0 (I5.0) and Society 5.0 (S5.0). This study aims to explore how these paradigms impact smart logistics operations within nanostores, focusing on the interplay between human-centric technologies and operational efficiency. A systematic meta-analysis, synthesizing 60 studies, and a detailed content analysis were employed to evaluate the integration of collaborative technologies, such as human-machine systems and human-robot collaboration, within nanostores’ logistics. Key findings reveal a notable shift from Industry 4.0, emphasizing the growing interaction between humans and technology, which enhances operational efficiency and customer satisfaction. The research is limited by the availability of empirical studies on I5.0 and S5.0 in nanostores, indicating the need for further investigation. The findings offer valuable insights for supply chain managers and business owners in nanostores, suggesting that adopting collaborative human-machine systems can significantly improve logistics outcomes. This research provides a novel framework for understanding the evolving role of human-technology collaboration in small retail environments and offers a roadmap for future research into smart logistics within these emerging paradigms.